Impact of the Electrolyte Co-Extraction to the Response of the Ionophore-based Ion-Selective Electrodes. (20th September 2016) - Ivanova, Anastasiya D.; Koltashova, Evgeniya S.; Solovyeva, Elena V.; Peshkova, Maria A.; Mikhelson, Konstantin N.
Graphical abstract: Highlights: Neutral-ionophore-based Ion-selective electrode. Simple theoretical model of the role of co-extraction in response. Experimental verification of the model using potassium electrode. Potentiometry, chronopotentiometry, impedance, UV-Vis spectra. Abstract: The impact of the aqueous electrolyte co-extraction to the potentiometric response of ionophore-based ion-selective electrodes (ISEs) is studied theoretically and experimentally. A simple theoretical model is developed to describe quantitatively how co-extraction of electrolytes influences the lower and the upper detection limits of ISEs. The theory is successfully verified with valinomycin-based K + -ISE as a model system, using potentiometric, chronopotentiometric, impedance and UV–vis measurements. A special (symmetric) setup of the galvanic cell is proposed which clearly demonstrates how co-extraction from the internal solution determines the lower detection limit of ISEs. The values of the partition coefficients of potassium salts used in the study are consistent with the respective Gibbs energies of anion transfer from water to organic phase. The model also gives a hint why the slope of real ISEs is typically slightly sub-Nernstian.